Beyond Brainstorming: Exploring Convergence in Teams - Seeber, Isabella; de Vreede, Gert-Jan; Maier, Ronald; Weber, Barbara (Journal of Management Information Systems, 2017)
Collaborative brainstorming is often followed by a convergence activity where teams extract the most promising ideas on a useful level of detail from the brainstorming results. Contrary to the wealth of research on electronic brainstorming, there is a dearth of research on convergence. We used experimental methods for an in-depth exploration of two facilitation-based interventions in a convergence activity: attention guidance (focusing participants on procedures to execute a convergence task) and discussion encouragement (engaging participants in conversations to combine knowledge on ideas). Our findings show that both attention guidance and discussion encouragement are correlated with higher convergence quality. We argue that attention guidance's contribution is in its support of coordination, information processing, and goal specification. Similar, we argue that discussion encouragement's contribution is in its stimulation of idea clarification and idea combination. Contrary to past research, our findings further show that satisfaction was higher after convergence than after brainstorming.